A Group-Based 8-Week Functional Interval-Type Outdoor Training Program Improves Physical Performance in Recreationally Active Adults - Anna Hendker; Eric Eils (Frontiers Media S.A., 2021)
Even though physical activity is an important aspect of health, lack of time or motivation impede people from working out regularly. One type of training program that is both efficient and motivating is functional interval-type outdoor training. To evaluate this, our study had 81 participants complete a battery of physical performance tests (incremental treadmill test, core stability test and functional fitness test) before and after an 8-week outdoor interval-type training intervention. Training procedures included multimodal and high-intensity exercises performed in consistent, small groups. Results showed that the interval training program produced significant increases in the intervention group (n = 43) in functional and strength exercises (p < 0.001; squat (+27%), burpee (+24%), bridge (+39%), push-up (+34%), sit-up (+25%), high knees (+25%), row (+19%), effect sizes 0.4-0.11) for almost all parameters in comparison to a non-intervention control population (n = 38). Interestingly, trunk stability increased significantly (p < 0.001; flexion (+86%), extension (+43%), lateral left (+39%), lateral right (+32%), effect sizes 0.3-0.15) even though it was not explicitly trained; this was rather a secondary outcome of the functional exercises. Drop-out rates (Intervention group: 27%) suggest that this form of training seems to improve adherence to exercise and may help participants to stay committed to regular, intense activity. By simultaneously triggering adaptations in functional fitness, endurance and whole-body movements, this program can be used by people at different training levels.